Myocardial infarction related to coronary embolism in a patient with prosthetic mitral valve thrombosis demonstrated by three- dimensional transesophageal echocardiography - (:unkn) unknown (My University, 2017)
Mekanik kapaklarla birlikte sistemik emboli insidansı yıllık %1'dir. Bakteriyel endokardit, kalp kapak hastalığı, kardiyomiyopatiler, atriyal miksoma, kardiyak aritmiler ve akut koroner sendrom koroner embolinin sebeblerindendir. Mekanik kapak trombozuna bağlı koroner emboli nadir görülmesine rağmen, önemli ve ciddi bir komplikasyondur. Koroner embolinin kanıta dayalı etkili bir tedavi ve yönetimi yoktur. Burada mekanik mitral kapak trombozuna bağlı koroner embolininin neden olduğu bir akut miyokard enfarktüsü vakası sunduk

The incidence of systemic embolization with mechanical valves is 1% per year. Bacterial endocarditis, valvular heart disease, cardiomyopathies, atrial myxoma, cardiac arrhythmias, and acute coronary syndrome are the causes of coronary embolism. Although coronary embolism due to mechanical valve thrombosis is encountered rarely, it is an important and serious complication. There is no evidence-based effective treatment and management of coronary embolism. Here we report a case of myocardial infarction caused by coronary embolism due to mechanical mitral valve thrombosis
Üç boyutlu transözofageal ekokardiyografi ile gösterilmiş protez mitral kapak trombüsü olan bir hastada koroner emboliye bağlı miyokard infarktüsü
Keywords: Genel ve Dahili Tıp